Pengaruh Return On Asset, Return On Equity, dan Earning Per Share terhadap Harga Saham - Alghi Fari, Faishal; Kurniawan, Budi (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
Capital markets help companies to finance their businesses. Investors invest in capital markets with the expectation of profit. Investors invest in capital markets with the expectation of profit. Investors consider financial performance in the form of financial metrics when investing capital. The purpose of this study is to examine the impact of Return on Assets (ROA), Return on Equity (ROE), and Earnings per Share (EPS) on stock prices of service sector companies listed on the Indonesian Stock Exchange (IDX). is to judge The period 2018-2021 is listed. The sample consists of 25 manufacturing companies selected using a targeted sampling method based on annual securities report data. Data were analyzed using multiple regression analysis using Eviews 10 for Windows. The results of this study show that the Return on Assets (ROA) and Return on Equity (ROE) variables have a negative impact and are insignificant. Earnings per share (EPS) has a positive impact and significant on stock prices